Accuracy of Clinical Diagnosis of Burst Appendix, a Study of 200 Cases in DMCH. (Medicine Today, 2021)
Introduction: Biochemical analysis or laboratory tests assist to determine what happening to the body internally. The aim of the present study was to access the biochemical features of type 2 diabetic patients in Kushtia district, Bangladesh.Materials and Methods: The cross-sectional study was conducted in type 2 diabetes mellitus patients who presented to the OPD in three referral diabetic centers in Kushtia district, Bangladesh from August 2016 to July 2017. A total of 282 patients were included in the study. The collected data were checked, entered and analyzed using the computer program Statistical Package for Social Sciences (SPSS) version 22.Results: Biochemical study showed that mean blood hemoglobin level was 12.49±1.47g/dl, mean fasting blood glucose level of the patients was 8.86±1.67mmol/L and blood glucose level two hours after breakfast was 13.94±2.88mmol/L. The study showed that the patient having abnormal level of triglyceride (66%) were higher than normal level (34%).Conclusion: The subjects had higher triglyceride and LDL values (65.6% and 28.7% respectively). These higher percentages with abnormal lipid profile are likely to be more prone to cardiovascular diseases.Medicine Today 2021 Vol.33(1): 75-79